Investigation of Hydraulic Characteristics and Fluid Dynamics in Sand Samples from the Osun River in Osogbo, Nigeria - Amoo, Afeez Oladeji; Adamu, Suleiman Bashir; Adeleye, Adeniyi Olarewaju (CV. Literasi Indonesia, 2025)
Understanding the natural flows in porous media with specific hydraulic characteristics is crucial for advancing science and engineering. This study examines the hydraulic properties and fluid dynamics of sand samples collected from eight locations along the Osun River bed at five-meter intervals in November 2023. Significant variations in hydraulic characteristics were identified by comparing the findings with international soil classification standards. The effective grain size ranged from 0.20 mm to 0.32 mm, with most samples between 0.30 mm and 0.31 mm. Sample F had the smallest grain size, indicating finer sand. Flow velocities varied from 1.57 cm/s to 2.41 cm/s, with the highest observed at locations B and E. Flow rates ranged from 1.23 × 10² cm³/s to 1.89 × 10² cm³/s, also highest at B and E. Reynolds numbers ranged from 1.39 × 106 to 8.58 × 106, indicating transitions from laminar to turbulent flow. Friction factors ranged from 7.46 × 106 to 45.85 × 106, with higher values at location A, indicating greater resistance to flow. Hydraulic gradients ranged from 1.09 to 1.83, and hydraulic conductivities were between 1.14 × 10-² cm/s and 1.43 × 10-² cm/s, with the highest observed at location A. The results align with recent research showing that coarser sands exhibit higher hydraulic conductivities and flow rates, whereas finer sands demonstrate greater resistance. The study underscores the importance of monitoring friction factors, flow velocity, flow rate, and Reynolds numbers to manage potential environmental hazards and water seepage through dams.